2014
DOI: 10.1038/nchembio.1481
|View full text |Cite
|
Sign up to set email alerts
|

Target identification for a Hedgehog pathway inhibitor reveals the receptor GPR39

Abstract: Hedgehog (Hh) signaling determines cell fate during development and can drive tumorigenesis. We performed a screen for new compounds that can impinge on Hh signaling downstream of Smoothened (Smo). A series of cyclohexyl-methyl aminopyrimidine chemotype compounds ('CMAPs') were identified that could block pathway signaling in a Smo-independent manner. In addition to inhibiting Hh signaling, the compounds generated inositol phosphates through an unknown GPCR. Correlation of GPCR mRNA expression levels with comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 48 publications
0
41
0
Order By: Relevance
“…Bassilana and coworkers have discovered a CMAP chemotype able to block GLI functions and, through a chemoproteomics strategy, they also have identified the orphan GPCR GPR39 as the specific target of this molecule [63]. Although the authors failed to demonstrate the direct binding of CMAP to GPR39, data document that CMAP is a specific agonist of this receptor.…”
Section: Indirect Gli Antagonistsmentioning
confidence: 94%
“…Bassilana and coworkers have discovered a CMAP chemotype able to block GLI functions and, through a chemoproteomics strategy, they also have identified the orphan GPCR GPR39 as the specific target of this molecule [63]. Although the authors failed to demonstrate the direct binding of CMAP to GPR39, data document that CMAP is a specific agonist of this receptor.…”
Section: Indirect Gli Antagonistsmentioning
confidence: 94%
“…Gene expression analysis suggested that GPR39 might be the target, consistent with specific gene knockdown and ultimately on-target dose–response studies with optimized compounds. A role for this oGPCR in modulation of the hedgehog pathway protein Gli was suggested 66 .…”
Section: New Chemistry For New Targetsmentioning
confidence: 99%
“…Noncovalent, lysate-based approaches have been successfully applied to the identification of a wide range of targets, including soluble enzymes such as protein kinases [5], the lipid kinase PIKFyve [11] and many others. However, a number of therapeutically relevant target families, in particular integral membrane proteins such as ion channels and G-protein-coupled receptors, are notoriously incompatible owing to loss of their binding-competent conformation during the experimental workflow [12,13].…”
Section: Affinity-based Approachesmentioning
confidence: 99%